Foxn3 is required to suppress aberrant ciliogenesis in nonphotoreceptor retinal neurons - Shuting Liu; Junyao Chen; Haiqiao Chen; Yanan Guo; Fa Yuan; Dongchang Xiao; Mengqing Xiang (Proceedings of the National Academy of Sciences, 2025)
The retinal photoreceptors possess specialized sensory cilia critical for phototransduction while the nonphotoreceptor cells typically exhibit simpler primary cilia or lack them altogether. This dichotomy in ciliary architecture underpins the functional specialization of retinal cell types, but how this dichotomy arises and is maintained remains elusive. This study explores the role of the transcription factor Foxn3 in establishing and maintaining this divergence. We generated retina-specific Foxn3 conditional knockout (Foxn3CKO) mice, which show that Foxn3 is essential for repressing ciliary gene expression in nonphotoreceptor cells, such as bipolar and amacrine cells. Foxn3CKO mice exhibit significant reductions in electroretinogram b-wave amplitudes and oscillatory potentials, indicating functional impairments in inner retinal neurons. Loss of Foxn3 leads to ectopic ciliary gene expression and abnormal ciliogenesis in nonphotoreceptor neurons, without affecting retinal cell specification and differentiation. Single-Cell RNA Sequencing, chromatin profiling, and transcription assays reveal that Foxn3 directly binds to and represses the promoters of ciliary genes and their transactivators, including Foxj1 and Rfx family members. Our data together highlight Foxn3 as a key transcriptional repressor that may function to ensure the proper ciliary architecture of retinal neurons by preventing nonphotoreceptor neurons from adopting photoreceptor-like ciliary features and provide insights into the molecular mechanisms governing retinal development and ciliopathies.